"BURSTING THE BUBBLE": Service learning in schools. (6th October 2020) - Pilling, Rachel; Mollaney, Jenna; Chandauka, Rumbidzai; Barai, Ishani; Parekh, Ravi
Abstract: Background: At Imperial College, we developed a novel teaching programme for medical students based within a local primary school, with the aim of developing students' teaching skills and centring social accountability in our curriculum. Similar service‐learning programmes have shown significant benefit for student participants, including: improving communication skills, developing an understanding of the social determinants of health, and increased empathy. In partnership with a local primary school, the programme involved a group of medical students designing, developing and delivering a teaching session to primary school children. Methods: Medical students completed written reflections on the programme and semi‐structured interviews were conducted with teachers who had participated in the programme. These were then thematically analysed. Results: Themes from student reflections included: improvement in teaching and communication skills; and an increased awareness of social accountability. Themes from teacher interviews included: benefits of an aspirational figure in the school; engagement of the children; and the ongoing inspirational benefit for the pupils. Discussion: Our analysis suggested students and the school community benefitted. Students reported the experience was an effective way to learn teaching skills and to improve their communication with children. The programme delivered skills transferrable to other clinical contexts including leadership and behavioural management, adaptability and creative thinking. Teacher interviews suggested the programme was mutually beneficial. The framing of medical students as role models raised the possibility that such programmes may help tackle the challenge of widening participation in medicine. We would recommend medical educators to consider developing other mutually beneficial service‐learning programmes.